Barriers faced by integrated health post cadres in stunting prevention among toddlers - pratiwi, Dwi citra; Diniyah, Kharisah (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Integrated Health Post cadres play a strategic role in stunting prevention efforts by monitoring the growth and development of toddlers, providing nutrition education, and mobilizing community participation. Globally, 250.2 million toddlers (23.2%) will experience stunting by 2024. In Indonesia, the stunting prevalence in 2024 remains at 19.8%, far below the national target of 14% by 2029. In Yogyakarta, the highest stunting prevalence is in Bantul Regency at 16.5%, with the Srandakan Community Health Center reporting a stunting percentage of 13.94% out of 1.028 toddlers. Purpose: To describe the role and challenges of Pos integrated health post cadres in stunting prevention. Method: This study used qualitative methods. Informants consisted of key informants (integrated health post cadre) and supporting informants (nutritionists and mothers of toddlers). Informants were selected using a purposive sampling method. Data collection was conducted through in-depth interviews using a structured interview guide and documentation. Data analysis included organizing the data, reading and reviewing the data, coding, developing theme descriptions, connecting themes, and interpreting the meaning of the themes. Results: This study indicates that cadres play a role in monitoring the nutritional status of toddlers, providing nutrition education, encouraging visits to the Integrated Health Post and mentoring mothers of toddlers at risk of stunting. However, the implementation of cadres' roles still faces several obstacles, including limited ongoing training, suboptimal support from health workers, and a lack of synchronization in nutrition data recording between integrated health post and Community Health Centers. Conclusion: Integrated health post cadres have fulfilled their role in stunting prevention, but this has not been optimal due to constraints in the service system and community participation. Suggestion: Increasing the capacity of cadres, strengthening coordination between health workers and cadres, and increasing community participation are needed to support successful stunting prevention.